Beliefs about using an outdoor pool: Understanding perceptions of place in the context of a recreational environment to improve health. (July 2015) - Middlestadt, Susan E.; Anderson, Austin; Ramos, William D.
Abstract: Following the Reasoned Action Approach, an online survey of 74 outdoor pool users illustrates how a theory-based behavioral analysis can be used to identify people׳s perceptions of a place in their environment. Regression analysis of close-ended data demonstrated that intention "to use the outdoor pool next summer season" was predicted ( R 2 =.636, p <.0001) from the weighted combination of attitude ( β =.663, p <.0001) and perceived control ( β =.197, p <.05). The importance of attitude suggests that use can be encouraged by addressing advantages. The content analysis of open-ended elicitation data revealed that users believed that pool use provides physical, social, and emotional advantages and could be made easier by modifying facility parameters. Implications for promoting and designing public health spaces to attract users to aquatic environments and to improve health are discussed.